2023
DOI: 10.1002/ijc.34718
|View full text |Cite
|
Sign up to set email alerts
|

qRT‐PCR analysis of CEACAM5, KLK6, SLC35D3, MUC2 and POSTN in colon cancer lymph nodes—An improved method for assessment of tumor stage and prognosis

Gudrun Lindmark,
Lina Olsson,
Basel Sitohy
et al.

Abstract: One fourth of colorectal cancer patients having curative surgery will relapse of which the majority will die. Lymph node (LN) metastasis is the single most important prognostic factor and a key factor when deciding on postoperative treatment. Presently, LN metastases are identified by histopathological examination, a subjective method analyzing only a small LN volume and giving no information on tumor aggressiveness. To better identify patients at risk of relapse we constructed a qRT‐PCR test, ColoNode, that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another complicating factor for the microscopic methods is selection of LNs for examination of presence of stem cells and assessment of stem cell numbers. The LNs of a single patient can differ considerably regarding the number of tumor cells and the risk factors these cells express ( 6 ). The fact that current guidelines for determination of metastasis status (pN-stage) requires examination of a minimum of 12 LNs points out the fact that LNs of one patient vary considerably in tumor burden ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another complicating factor for the microscopic methods is selection of LNs for examination of presence of stem cells and assessment of stem cell numbers. The LNs of a single patient can differ considerably regarding the number of tumor cells and the risk factors these cells express ( 6 ). The fact that current guidelines for determination of metastasis status (pN-stage) requires examination of a minimum of 12 LNs points out the fact that LNs of one patient vary considerably in tumor burden ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker mRNA analysis is a very promising alternative allowing analysis of the entire LN volume and analysis of a combination of biomarkers that characterize different properties of the tumors that can be combined in a kit. ColoNode, which combines analysis of mRNAs of CEA (CEACAM5), Kallikrein Related Peptidase 6 (KLK6), Solute Carrier Family 35 Member D3 (SLC35D3), Mucin 2 (MUC2) and Periostin (POSTN) of half the LN volume is a successful colon cancer (CC) prognostic test that surpasses histopathology in identifying patients that will relapse and in addition grades patients with different degrees of risk ( 6 ). The study identified two distinct group of patients, one which should be recommended postoperative adjuvant treatment and another which should be left untreated.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer remains a non-negligible cause of cancer-related death ( 16 - 18 ). Surgical therapy is less effective in advanced colorectal cancer patients than those early patients ( 19 ). Additional therapy is required to delay the progression of colorectal cancer, including cell proliferation suppression, apoptosis facilitation, and cell migration inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…POSTN is, however, not expressed in the tumor cells. Still, elevated POSTN mRNA levels in LNs from CC patients is an important contributor in ColoNode assay being one of five biomarkers in the two-triplex assay for prediction of tumor recurrence in CC ( 37 ).…”
Section: Discussionmentioning
confidence: 99%